Right and Left Weyl Operator Matrices in a Banach Space Setting - Aichun Liu; Junjie Huang; Alatancang Chen (Journal of Mathematics)
Let Xi,Yii=1,2 be Banach spaces. The operator matrix of the form MC=AC0B acting between X1⊕X2 and Y1⊕Y2 is investigated. By using row and column operators, equivalent conditions are obtained for MC to be left Weyl, right Weyl, and Weyl for some C∈ℬX2,Y1, respectively. Based on these results, some sufficient conditions are also presented. As applications, some discussions on Hamiltonian operators are given in the context of Hilbert spaces.